Oxidative stress and micronutrients in leprosy - Oliveira, Fabiana Maciel de; Barbosa Junior, Fernando; Jordao Junior, Alceu Afonso; Foss, Norma Tiraboschi; Navarro, Anderson Marliere [UNESP]; Cipriani Frade, Marco Andrey (Pontificia Universidade Catolica Campinas, 2015)
Objective To determine the oxidative stress and the antioxidant and micronutrient profile of patients with multibacillary and paucibacillary leprosy before polychemotherapeutic treatment. Methods Thirty control samples and fifty-two serum samples from leprosy patients who attended the dermatology outpatient clinic of a public university hospital were analyzed; 38 of them had multibacillary and 14 paucibacillarty. Malondialdehyde, a marker of lipid peroxidation, was determined using the thiobarbituric acid reacting substances assay; the antioxidant reduced glutathione was determined using a method based on the quantification of acid-soluble thiol; the antioxidant vitamin E was determined using High-Performance Liquid Chromatography; the minerals selenium, zinc, copper and magnesium were determined using coupledmass spectrometry, and the serum phenol I glycolipid antibody was determined using Enzyme-Linked Immunosorbent Assay. The nonparametric Mann-Whitney test was used to compare the variables quantified in the present study between the different groups, and Pearson's correlation analysis was used to verify the association between these variables and the antibody. The significance level was set at p<0.05. Results There was a significant difference in the content of malondialdehyde (p<0.001) and vitamin E (p<0.001) between the groups with multibacillary and paucibacillary leprosy (p=0.495 and p=0.920, respectively) and the control groups. Reduced glutathione levels were higher in the control group compared with those of the group with leprosy (p=0.012) and multibacillary leprosy (p=0.001), but did it not differ from that of the paucibacillary group (p=0.920). Reduced glutathione levels did not differ between the multibacillary and paucibacillary groups (p=0.063) either. All minerals were within normal limits, except for magnesium; magnesium deficiency was detected in all groups studied. No correlation was observed between the anti-phenolic glycolipid I antibody and the remaining variables. Conclusion Paucibacillary patients seem to have more pronounced reduced glutathione antioxidant defense, similar to that of healthy individuals. The low vitamin E levels of leprosy patients suggest the benefits of supplementation. The metabolic changes observed did not demonstrate an association with anti-phenolic glycolipid I serology.
Keywords: Antioxidants; Oxidative stress; Leprosy; Micronutrients